The history of the development and stages of development of Psychological Science - Isaeva Guli Parpievna (Peerian Journals Publishing, 2022)
In this article, the concept of psychology, the history of the development and stages of development of Psychological Science information is provided.
Keywords: psychology; development; scientific psychology; behavior